Osteopathic Manipulative Treatment Limits Chronic Constipation in a Child with Pitt-Hopkins Syndrome - Alessandro Aquino; Mattia Perini; Silvia Cosmai; Silvia Zanon; Viviana Pisa; Carmine Castagna; Stefano Uberti (Case Reports in Pediatrics)
Pitt-Hopkins Syndrome (PTHS) is a rare genetic disorder caused by insufficient expression of the TCF4 gene. Children with PTHS typically present with gastrointestinal disorders and early severe chronic constipation is frequently found (75%). Here we describe the case of a PTHS male 10-year-old patient with chronic constipation in whom Osteopathic Manipulative Treatment (OMT) resulted in improved bowel functions, as assessed by the diary, the QPGS-Form A Section C questionnaire, and the Paediatric Bristol Stool Form Scale. The authors suggested that OMT may be a valid tool to improve the defecation frequency and reduce enema administration in PTHS patients.